Substituent Effects on the Thermodynamic Stability of Imines Formed from Glycine and Aromatic Aldehydes: Implications for the Catalytic Activity of Pyridoxal-5'-Phosphate (PLP) - Crugeiras, Juan (2009)
Equilibrium constants for addition of glycine to substituted benzaldehydes to form the corresponding imines and pK(a)s for ionization of the iminium ions were determined by (1)H NMR analysis in D(2)O. The introduction of a phenoxide anion substituent into the aromatic ring of benzaldehyde leads to a substantial increase in the pK(a) of the iminium ion from 6.3 to 10.2 for p-hydroxybenzaldehyde and to 12.1 for salicyaldehyde. An analysis of the differential effect of ortho- versus para-substitution shows that the iminium ion to salicylaldehyde is stabilized by an intramolecular hydrogen bond in aqueous solution, with an estimated energy ca. 3 kcal/mol larger than can be accounted for by a simple electrostatic interaction. A comparison of the o-O(−) substituent effect on the acidity of the iminium ions of glycine to benzaldehyde and 4-pyridine-carboxaldehyde provides evidence for the existence of an internal hydrogen bond of similar strength in pyridoxal 5'-phosphate (PLP) iminium ions in water. The effects of other ring substituents on the stability of PLP iminium ions are discussed.